Intensification of Thermal Convection near Electric Devices using Flat Screens – Computer Modelling - Czapp, S.; Czapp, M. (Elektronika ir Elektrotechnika, 2013)
Intensification of natural thermal convection near electric devices is possible by application of additional elements as screens creating convection canals close to the device. In the earlier authors paper the results of the analysis of thermal convection with the use of only one additional screen close to the electric device were presented. This paper presents computer modelling of thermal convection when two screens near the electric device are implemented. One of the screen is a wall close to the electric device. DOI: http://dx.doi.org/10.5755/j01.eee.19.2.3462